Copper selenide / tricalcium silicate bone cement

By introducing copper selenide nanoparticles into tricalcium silicate bone cement, the problems of low compressive strength and rapid degradation rate were solved, higher compressive strength and degradation control were achieved, and combined with near-infrared technology, a new treatment strategy for bone tumors was provided.

CN120695251APending Publication Date: 2025-09-26THE 940TH HOSPITAL OF THE CHINESE PEOPLES LIBERATION ARMY JOINT LOGISTICS SUPPORT FORCE
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510701486.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-28
Publication Date
2025-09-26

AI Technical Summary

Technical Problem

Existing tricalcium silicate bone cement has low compressive strength and a fast degradation rate, which is difficult to meet the needs of bone tumor treatment.

Method used

By introducing a small amount of copper selenide nanoparticles into tricalcium silicate bone cement, the compressive strength can be improved and the degradation rate can be reduced by adjusting its shape, particle size and proportion.

Benefits of technology

The introduction of copper selenide nanoparticles not only shortens the hydration and coagulation time, reduces the porosity and degradation rate, but also improves the compressive strength and has temperature-increasing properties under near-infrared light, thereby enhancing the therapeutic effect on bone tumors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120695251A_ABST
    Figure CN120695251A_ABST
Patent Text Reader

Abstract

The invention discloses copper selenide / tricalcium silicate bone cement. The bone cement comprises a liquid phase component and a solid phase component, the liquid phase component is water, and the solid phase component is tricalcium silicate powder and copper selenide nanoparticles. Compared with the existing tricalcium silicate bone cement, the tricalcium silicate bone cement has the advantages that by introducing a trace amount of copper selenide nanoparticles, not only can the hydration and coagulation time of tricalcium silicate be shortened, but also the porosity and degradation rate of the tricalcium silicate after coagulation and solidification can be reduced, the compressive strength can be improved, the stimulation effect on ALP activity of MC3T3-E1 cells can be enhanced, the survival rate of the MC3T3-E1 cells can be improved, and the application prospect is broad. The immunogenic apoptosis of K7M2-wt cells is promoted, and the tumor growth rate is reduced. Besides, the introduction of the copper selenide nanoparticles can also endow the tricalcium silicate bone cement with the performance of temperature rise under near-infrared light, so that in clinical application, the tricalcium silicate bone cement can be further combined with a near-infrared technology to realize ablation of bone tumors, and a new strategy is provided for treatment of the bone tumors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of medical tricalcium silicate bone cement, and particularly relates to copper selenide / tricalcium silicate bone cement. Background Art

[0002] As an excellent filling material, bone cement has extremely important application value in the treatment of bone tumors, vertebral metastases, etc. Many types of bone cement have been developed, including polymethyl methacrylate bone cement, calcium phosphate bone cement, calcium silicate bone cement, calcium sulfate bone cement, magnesium phosphate bone cement, etc. Calcium silicate bone cement has attracted extensive attention and research from scientific researchers because of its good biological activity, biodegradability, low heat release during the self-curing process, injectable paste, porous structure of the cured product, ability to induce hydroxyapatite deposition on its surface, and excellent bone conduction properties. Currently, the most studied calcium silicate bone cement is tricalcium silicate. However, the existing tricalcium silicate bone cement has the disadvantages of low compressive strength and fast degradation rate after hydration and solidification. Summary of the Invention

[0003] In order to overcome the shortcomings of existing tricalcium silicate bone cement, the present invention provides a copper selenide / tricalcium silicate bone cement, which improves the compressive strength of existing tricalcium silicate bone cement and reduces its degradation rate by introducing copper selenide nanoparticles.

[0004] To achieve the above object, the present invention adopts the following technical solutions: A copper selenide / tricalcium silicate bone cement comprises a liquid phase component and a solid phase component, and is characterized in that the liquid phase component is water, and the solid phase component is tricalcium silicate powder and copper selenide nanoparticles.

[0005] Preferably, the molecular formula of the copper selenide nanoparticles is Cu 2-x Se,0 <x<1。

[0006] Preferably, the copper selenide nanoparticles are circular and / or elliptical in shape.

[0007] Preferably, the particle size of the copper selenide nanoparticles is 3-5 nm.

[0008] Preferably, the copper selenide nanoparticles are obtained by reacting selenium powder, sodium borohydride and copper salt in the presence of polyvinyl pyrrolidone.

[0009] More preferably, the molar ratio of the selenium powder, sodium borohydride and copper salt is 0.5:1.5:1, and the mass ratio of the polyvinyl pyrrolidone to selenium powder is 1:1.

[0010] More preferably, the copper salt is copper chloride or copper sulfate.

[0011] Preferably, the mass average molecular weight of the polyvinyl pyrrolidone is 50,000-60,000.

[0012] Preferably, the mass ratio of the tricalcium silicate powder to the copper selenide nanoparticles is 10000:1-40.

[0013] More preferably, the mass ratio of the tricalcium silicate powder to the copper selenide nanoparticles is 10000:5-40.

[0014] Most preferably, the mass ratio of the tricalcium silicate powder to the copper selenide nanoparticles is 10000:10-20.

[0015] Preferably, the liquid-to-solid ratio is 0.1-1 mL / g.

[0016] More preferably, the liquid-to-solid ratio is 0.5 mL / g.

[0017] The copper selenide / tricalcium silicate bone cement is used in the preparation of a substitute material for treating bone tumors or postoperative bone transplantation.

[0018] Beneficial effects The present invention introduces a trace amount of copper selenide nanoparticles into the existing tricalcium silicate bone cement, which can not only shorten the hydration and coagulation time of the tricalcium silicate, but also reduce its porosity and degradation rate after coagulation and solidification, and improve the compressive strength.

[0019] The results of in vitro cytocompatibility experiments showed that the introduction of trace amounts of copper selenide nanoparticles into tricalcium silicate bone cement could enhance the stimulation of ALP activity in MC3T3-E1 cells, increase the survival rate of MC3T3-E1 cells, and promote the immunogenic apoptosis of K7M2-wt cells.

[0020] The results of animal experiments showed that after introducing a trace amount of copper selenide nanoparticles into tricalcium silicate bone cement, the tumor growth rate was significantly reduced and the levels of CRT protein and HMGB-1 protein were improved.

[0021] The introduction of copper selenide nanoparticles can also give tricalcium silicate bone cement the property of increasing temperature under near-infrared light, so that in clinical applications, near-infrared technology can be further combined to achieve ablation of bone tumors, providing a new strategy for the treatment of bone tumors. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Transmission electron microscopy image of copper selenide nanoparticles.

[0023] Figure 2 This is the XPS spectrum of copper selenide nanoparticles.

[0024] Figure 3 This is the XRD pattern of copper selenide nanoparticles.

[0025] Figure 4 XRD patterns of different bone cement test samples.

[0026] Figure 5 Scanning electron microscopy images of different bone cement test samples.

[0027] Figure 6 Final setting time of different bone cement slurries under saturated water vapor at 37°C (A) and NIR irradiation (B).

[0028] Figure 7 The compressive strength of samples tested for different bone cements.

[0029] Figure 8 The porosity of the samples was tested for different bone cements.

[0030] Figure 9 Degradation rates of different bone cement test samples.

[0031] Figure 10 Temperature curves of different bone cement slurries under NIR irradiation from 0 to 600 seconds.

[0032] Figure 11 is the compressive strength of different bone cement slurries after NIR irradiation.

[0033] Figure 12 Temperature curves of different bone cement test samples under NIR irradiation from 0 to 600 seconds.

[0034] Figure 13 The results of culturing MC3T3-E1 cells in bone cement extracts with different concentrations are shown.

[0035] Figure 14 CS and CS-20Cu diluted 1 / 64 2-x Effect of Se cement extract on ALP activity of MC3T3-E1 cells.

[0036] Figure 15 For CS and CS-20Cu 2-x Effects of Se bone cement test samples on ATP release from K7M2-wt cells.

[0037] Figure 16 For CS and CS-20Cu 2-x Effects of Se bone cement test samples on CRT protein immunofluorescence in K7M2-wt cells.

[0038] Figure 17 For CS and CS-20Cu 2-x Effects of Se bone cement test samples on HMGB-1 protein immunofluorescence in K7M2-wt cells.

[0039] Figure 18 CS group (A) and CS-20Cu under NIR irradiation 2-x Se group (B) Photothermal images of nude mice from 0 to 600 s.

[0040] Figure 19 This is the temperature curve of the tumor in nude mice under NIR irradiation.

[0041] Figure 20 CS group and CS-20Cu under NIR irradiation and non-NIR irradiation 2-x Changes in tumor volume of nude mice in the Se group.

[0042] Figure 21 CS group and CS-20Cu group after 14 days under NIR irradiation and non-NIR irradiation 2-x Tumor tissue sections of nude mice in the Se group.

[0043] Figure 22 CS group and CS-20Cu group after 14 days under NIR irradiation and non-NIR irradiation 2-x Results of CRT protein immunohistochemical analysis of nude mice in the Se group.

[0044] Figure 23 CS group and CS-20Cu group after 14 days under NIR irradiation and non-NIR irradiation 2-x Results of immunohistochemical analysis of HMGB-1 protein in nude mice in the Se group.

[0045] Figure 24 Non-tumor bearing male nude mice were intraperitoneally injected with cement extract and their viscera were sliced ​​after 7 days of feeding. DETAILED DESCRIPTION

[0046] Various exemplary embodiments of the present invention are now described in detail. This detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention. It should be understood that the terms used in the present invention are only for describing specific embodiments and are not intended to limit the present invention.

[0047] In addition, for numerical ranges in the present invention, it is understood that each intervening value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between any stated value or stated range, and any other stated value or intervening value in the stated range, is also included in the present invention. The upper and lower limits of these smaller ranges may independently be included or excluded in the range.

[0048] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention pertains. Although preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein can also be used in the practice or testing of the present invention.

[0049] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0050] Data analysis in the embodiments of the present invention was performed using SPSS (IBM version 21) to process experimental data. Normal distribution data were presented. For continuous normal distribution parameters, independent sample t tests were used to analyze the differences between the data. When P < 0.05, the data were considered statistically different.

[0051] Example 1 (1) Preparation of copper selenide nanoparticles Transfer 39.48 mg of selenium powder to a 100 mL three-necked flask, add 48 mL of deionized water, and stir (200 rpm, room temperature) for 30 minutes. Simultaneously, high-purity nitrogen was introduced into the flask to remove oxygen from the system and maintain a vacuum. Once oxygen was completely eliminated, slowly pipette 2 mL of sodium borohydride (56.75 mg) in water and stir (700 rpm, room temperature) for 120 minutes. Then, quickly pipette 2 mL of a mixed aqueous solution of copper chloride (134 mg) and polyvinylpyrrolidone (40 mg, Mw ~55,000) in water, and stir at room temperature (1250 rpm) for 60 minutes. After completion of the reaction, transfer the reaction solution to a dialysis bag (Mwco = 10,0000) and dialyze against deionized water for 48 hours, while maintaining a stirring speed of 200 rpm. After dialysis, the solution was transferred to a 50 mL centrifuge tube, placed in a -80 °C refrigerator for 5 h, and then freeze-dried in a freeze dryer into a flocculent powder to obtain copper selenide nanoparticles.

[0052] Figure 1 This is a transmission electron micrograph of copper selenide nanoparticles. Horizontal lattice fringes can be seen under the TEM. The particles are also clearly round or oval in shape. The scale bar measures their diameters between 3nm and 5nm.

[0053] Figure 2 This is the XPS spectrum of copper selenide nanoparticles. It can be seen that Cu element appears Cu + and Cu 2+There are two obvious peaks, indicating that Cu is not present as Cu (I) or Cu (II). 2- The presence of a peak in the C spectrum confirms its presence in the negative divalent state. The presence of a distinct C peak in the C spectrum is due to the addition of polyvinylpyrrolidone as a stabilizer during the copper selenide preparation process. Based on the above, the copper selenide nanoparticles we prepared can be initially determined to be a mixture of CuSe and Cu2Se.

[0054] Figure 3 The XRD pattern of copper selenide nanoparticles is compared with the JCPDS card and combined with the conclusions obtained by XPS, the molecular formula of copper selenide nanoparticles can be determined to be Cu 2-x Se.

[0055] (2) Effects of copper selenide nanoparticles on the physical and chemical properties of tricalcium silicate bone cement In a 10 mL centrifuge tube, 2-x Se nanoparticles were mixed with deionized water at a ratio of 0.2 mg / mL, 1 mg / mL, 2 mg / mL, 4 mg / mL, and 8 mg / mL, respectively, and the mixed solution was ultrasonically vibrated for 12 min to obtain uniformly dispersed Cu nanoparticles with different concentrations. 2-x Se aqueous solution. Then Cu 2-x Se aqueous solution was mixed with tricalcium silicate (CS) powder at a liquid-powder ratio of 0.5 mL / g and stirred thoroughly to obtain different Cu 2-x Se / CS ratio of bone cement slurry.

[0056] The above-mentioned different bone cement slurries were respectively injected into polyethylene tetrafluoroethylene molds, and then placed in a constant temperature and humidity incubator. After curing for 5 hours under water vapor saturation at 37°C, the molds were demolded and continued to cure under the same conditions for 24 hours. Bone cement test samples with a diameter × height of 10 × 2 mm (round cake shape) were obtained.

[0057] Table 1 Raw material ratios of different bone cement test samples

[0058] Figure 4 The XRD patterns of different bone cement test samples are compared with the JCPDS cards. The diffraction peaks of unreacted tricalcium silicate crystals (C3S) and calcium hydroxide (CH) produced after hydration can be seen. Overall, compared with the control sample CS, CS-1Cu 2-x Se, CS-5Cu 2-x The Ca(OH)2 diffraction peak of Se does not show obvious differences. 2-x Se, CS-20Cu 2- xSe、CS-40Cu2-x The Ca(OH)2 diffraction peak of Se is higher than that of CS, especially the diffraction peak intensity at 18 degrees is more obvious. This may be due to the mass ratio of 10 / 10,000-40 / 10,000 nanometers of Cu 2-x The addition of Se promotes the crystallization of Ca(OH)2. 2-xS e and CS-20Cu 2-x The Ca(OH)2 diffraction peaks of Se are higher than those of CS-40Cu 2-x Se, this may be due to the excessive concentration of (40 / 10,000) Cu 2-x Se nanoparticles have inhibited the crystallization of Ca(OH)2.

[0059] Figure 5 The scanning electron microscope images of different bone cement test samples are shown. 2-x Se, CS-5Cu 2- x Se, CS-10Cu 2-x Se, CS-20Cu 2-x Se, CS-40Cu 2-x The Se sample is mainly composed of relatively uniform 5 to 10 micron block particles with a relatively obvious porous structure. These block particles may be agglomerated by smaller unhydrated CS and hydration products Ca(OH)2 and CSH. Small needle-shaped crystals appear around the particles, reflecting the typical characteristics of CSH in the early stage of hydration. This may be due to the Cu 2-x Se particles are small and have low content, so Cu is not directly observed under the electron microscope. 2-x Se.

[0060] Figure 6 (A) is the final setting time of different bone cement slurries. The average final setting time of pure CS cement slurry is 156 minutes, while CS-1Cu 2-x Se, CS-5Cu 2-x Se, CS-10Cu 2-x Se, CS-20Cu 2-x Se, CS-40Cu 2-x The average final setting time of Se is 153, 151, 135, 128 and 113 min respectively. 2-x With the increase of Se content, CS-Cu 2-x The final setting time of Se cement gradually decreases.

[0061] Figure 7 The compressive strength of different bone cement test samples. 2-xAs Se content increases, the compressive strength gradually increases from an average of 17.85 MPa (CS) to an average of 20.06 MPa (CS-5Cu 2-x Se), 20.64Mpa(CS-10Cu 2-x Se), 30.21Mpa(CS-20Cu 2-x Se), when Cu 2-x When the Se content is 40 / 10,000, it drops to an average of 21.21Mpa (CS-40Cu 2- x Se).

[0062] Figure 8 The porosity of different bone cement samples was tested. 2-x As Se content increases, the porosity gradually decreases from an average of 24.0% (CS) to 23.6% (CS-1Cu 2-x Se), 18.9% (CS-5Cu 2-x Se), 18.2% (CS-10Cu 2-x Se), 16.5% (CS-20Cu 2-x Se), when Cu 2-x When the Se content is 40 / 10,000, it increases to an average of 18.4% (CS-40Cu 2-x Se).

[0063] Figure 9 The degradation rate of different bone cement test samples (test method: the above bone cement test samples were placed in a vacuum freeze drying box and dried for 72 hours to constant weight. The surface area of ​​Tris-HCl solution and sample was 10ml / cm 2 Add the mixture into a blue-mouth bottle in a constant temperature water bath shaker. Take out the sample every 5 days, wash, dry, weigh, record, and replace with new Tris-HCl. 2-x Se, CS-20Cu 2-x Se, CS-40Cu 2-x The degradation rate of Se did not show significant differences. 2-x Se, CS-20Cu 2-x Se, CS-40Cu 2-x The degradation rate of Se was significantly lower than that of CS. 2-x Se (25.43%) and CS-40Cu 2-x Se (30.16%), CS-20Cu 2-x Se (23.57%) showed the lowest degradation rate.

[0064] The present invention also examined the near infrared laser (NIR, 808nm, power 891mw·cm -2 ) on the effects of irradiation on the different bone cement slurries and round bone cement test samples. The results are as follows: Figure 10 The temperature curves of different bone cement slurries under NIR irradiation within 0-600s. 2-x Se, CS-5Cu 2-x Se, CS-10Cu 2-x Se, CS-20Cu 2-x Se, CS-40Cu 2-x The temperature of Se increases and stabilizes at 200s until the end of irradiation. 2-x As Se content increases, the temperature change also increases. This shows that Cu 2-x The introduction of Se gives CS bone cement photothermal properties, and this photothermal property already exists in the cement slurry. 2-x Se and CS-40Cu 2-x The elevated temperature of the Se cement slurry has reached a level capable of ablating tumors, potentially enabling the ablation of osteosarcomas when combined with near-infrared light. Photothermal therapy can be achieved without waiting for the cement to fully solidify, potentially allowing for early irradiation therapy after cement slurry injection in clinical practice.

[0065] Figure 6 (B) is the final setting time of different bone cement slurries under NIR irradiation. Due to the photothermal properties of composite cement, the setting and curing process of cement increases with the increase of Cu 2-x The increase of Se content is significantly accelerated. 2-x The average final setting time of Se is only 65 min, which is significantly shorter than that of the unirradiated state (113 min). 2-x Se, CS-10Cu 2-x Se and CS-20Cu 2-x The average final setting time of Se was significantly shortened to 144, 123 and 93 min.

[0066] Figure 11 is the compressive strength of different bone cement slurries after NIR irradiation (irradiation time is 1h). 2-x As Se content increases, the compressive strength gradually increases from an average of 0.19 MPa (CS) to an average of 0.23 MPa (CS-5Cu 2-x Se), 0.31Mpa(CS-10Cu 2-x Se), 1.21Mpa(CS-20Cu2-x Se), 1.61Mpa (CS-40Cu 2-x Se). This may be related to the fact that the heat generated by NIR irradiation accelerates the CS-Cu 2-x The coagulation process of Se cement slurry is related to the degree of hydration.

[0067] Figure 12 The temperature curves of different bone cement test samples under NIR irradiation from 0 to 600 seconds are shown. The temperature of each round cake test sample increases with the increase of NIR irradiation time and tends to be stable at 200 seconds until the end of irradiation. 2-x As the Se content increases, the temperature change also increases. This also shows that Cu 2-x The introduction of Se endows CS bone cement with photothermal properties, and CS-Cu 2-x Se cement still has excellent photothermal conversion ability after solidification. Among them, the photothermal performance results of the same slurry are similar, CS-20Cu 2-x Se and CS-40Cu 2-x The temperature of the Se cake test sample has been raised to a level that can ablate the tumor.

[0068] (3) Biological activity test 3.1 Effects of MC3T3-E1 cell proliferation and alkaline phosphatase activity Evaluation of CS-Cu according to ISO 10993-5 2-x In vitro cell compatibility of Se bone cement. 2-x The Se test sample was ground into powder and passed through a 300-mesh sieve. After weighing, the powder was mixed with the volume of MEM-α culture medium at a ratio of 200 mg / mL and then immersed in MEM-α basal culture medium at 37°C for 24 h to prepare CS and CS-Cu2 -x Se extract. Since high temperature and high pressure sterilization may affect Cu 2-x To ensure the stability of Se nanocrystals, the cement extract was sterilized by filtration and then diluted with MEM-α (1 / 512, 1 / 256, 1 / 128, 1 / 64, 1 / 32, 1 / 16, 1 / 8, 1 / 4, and 1 / 2) to obtain culture solutions of different concentrations.

[0069] Figure 13 The results of culturing MC3T3-E1 cells in the above-mentioned culture medium with different concentrations are shown in Figure 2. 2-x The survival rates of Se cement extracts were higher than those of the blank control group (MEM-α).

[0070] Figure 14CS and CS-20Cu diluted 1 / 64 2-x The effect of Se cement extract on the alkaline phosphatase (ALP) activity of MC3T3-E1 cells can be seen. 2-x Se has a better stimulating effect on ALP activity in MC3T3-E1 cells than CS.

[0071] 3.2 Effect of immunogenic apoptosis on K7M2-wt cells Figure 15 For CS and CS-20Cu 2-x Effects of Se bone cement test samples on ATP release from K7M2-wt cells. CS group and CS-20Cu 2-x The average levels of ATP secreted by K7M2-wt cells treated with Se were 133.25umol / gprot and 257.44umol / gprot respectively. 2-x The average levels of the Se+NIR group were 172.85umol / gprot and 421.03umol / gprot respectively.

[0072] Figure 16 For CS and CS-20Cu 2-x Effects of Se bone cement test samples on CRT protein immunofluorescence in K7M2-wt cells. 2-x The average relative fluorescence intensities of the Se and CS groups were 0.1475 and 0.1261, respectively. 2-x The average relative fluorescence intensities of the Se+NIR group and CS+NIR group were 0.1780 and 0.1396, respectively.

[0073] Figure 17 For CS and CS-20Cu 2-x Effects of Se bone cement test samples on HMGB-1 protein immunofluorescence in K7M2-wt cells. 2-x The average relative fluorescence intensities of the Se and CS groups were 0.0489 and 0.0563, respectively. 2-x The average relative fluorescence intensities of the Se+NIR group and CS+NIR group were 0.0430 and 0.0521, respectively.

[0074] (4) Animal experiments (ablation of osteosarcoma) 100 μL of cell dilution was injected subcutaneously under the right forelimb of each nude mouse. A visible tumor grew in about 3-5 days. The tumor was measured every day and the tumor volume (mm 3 ) = tumor length (mm) × tumor width (mm)2 ÷2. When the tumor volume grows to 50 mm 3 When 0.05 ml of the above CS and CS-20Cu were injected respectively 2-x Se cement slurry.

[0075] Figure 18 CS group (A) and CS-20Cu under NIR irradiation 2-x Photothermal images of nude mice in group Se (B) from 0 to 600 s, and the temperature curve at the corresponding tumor is shown in Figure 2. Figure 19 As shown in Figure 2, under NIR irradiation, the average temperature of the tumor in the nude mice in the CS group increased from 36.3°C to 39.4°C, with an average temperature change of 3.1°C. 2-x The average temperature of the tumor site in nude mice in the Se group increased from 35.9°C to 50.8°C, with an average temperature change of 14.9°C, which was nearly 5 times that of the CS group.

[0076] Figure 20 CS group and CS-20Cu under NIR irradiation and non-NIR irradiation 2-x Tumor volume changes of nude mice in the Se group. The tumor in the CS group increased to 820 mm on the 14th day. 3 , it had grown to 1023 mm before being killed by dislocation on the 15th day. 3 The tumor size of the CS+NIR group was 179 cm on day 14. 3 ,CS-20Cu 2-x The size of the tumor in the Se group was 303 cm on day 14. 3 , indicating that the introduction of Cu 2-x Se can significantly reduce the growth rate of tumors. In contrast to the other groups with significantly increased tumor volume, CS-20Cu 2-x The tumor volume of nude mice in the Se+NIR group showed a trend of shrinking, shrinking to 46 mm on the 14th day. 3 (less than 50mm 3 ).

[0077] Figure 21 CS group and CS-20Cu group after 14 days under NIR irradiation and non-NIR irradiation 2-x Tumor tissue sections of nude mice in the Se group. CS-20Cu 2-x The Se+NIR group showed a significantly loosened structure, with numerous tumor cells undergoing necrosis and lysis, a high number of cell fragments, a significant decrease in cell number, inflammatory cell infiltration, and hemorrhage. The other groups showed intact tumor tissue structure, dense and uniform cell arrangement, a high overall cell number, and no inflammatory cell infiltration.

[0078] Figure 22CS group and CS-20Cu group after 14 days under NIR irradiation and non-NIR irradiation 2-x Results of CRT protein immunohistochemical analysis of nude mice in Se group. 2-x Se+NIR group, CS-20Cu 2-x The average relative fluorescence intensities of the Se group, CS+NIR group, and CS group were 0.4988, 0.2896, 0.2993, and 0.1988, respectively.

[0079] Figure 23 CS group and CS-20Cu group after 14 days under NIR irradiation and non-NIR irradiation 2-x Results of immunohistochemical analysis of HMGB-1 protein in nude mice in Se group. 2-x Se+NIR group, CS-20Cu 2-xS The average relative fluorescence intensities of group e, group CS+NIR, and group CS were 0.1985, 0.2987, 0.2760, and 0.3896, respectively.

[0080] (4) Biosafety Figure 24 Two groups of non-tumor bearing male nude mice were intraperitoneally injected with the above CS and CS-20Cu 2-x The rats were treated with 100 μL of Se extract and fed with conventional methods for 7 days. No obvious abnormalities were found in the heart, liver, spleen, lung, and kidney after HE staining.

[0081] The embodiments described above are merely descriptions of preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Without departing from the spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by persons skilled in the art should fall within the scope of protection defined by the claims of the present invention.

Claims

1. A copper selenide / tricalcium silicate bone cement comprising a liquid phase component and a solid phase component, characterized in that: The liquid phase component is water, and the solid phase component is tricalcium silicate powder and copper selenide nanoparticles.

2. The copper selenide / tricalcium silicate bone cement according to claim 1, characterized in that: The molecular formula of the copper selenide nanoparticles is Cu 2-x Se,0 <x<1。 3. The copper selenide / tricalcium silicate bone cement according to claim 1, wherein: The copper selenide nanoparticles are circular and / or elliptical in shape.

4. The copper selenide / tricalcium silicate bone cement according to claim 1, characterized in that: The particle size of the copper selenide nanoparticles is 3-5 nm.

5. The copper selenide / tricalcium silicate bone cement according to claim 2, characterized in that: The copper selenide nanoparticles are obtained by reacting selenium powder, sodium borohydride and copper salt in the presence of polyvinyl pyrrolidone.

6. The copper selenide / tricalcium silicate bone cement according to claim 5, characterized in that: The molar ratio of the selenium powder, sodium borohydride and copper salt is 0.5:1.5:1, and the mass ratio of the polyvinyl pyrrolidone to the selenium powder is 1:

1. Preferably, the copper salt is copper chloride or copper sulfate.

7. The copper selenide / tricalcium silicate bone cement according to claim 5, characterized in that: The mass average molecular weight of the polyvinyl pyrrolidone is 50,000-60,000.

8. The copper selenide / tricalcium silicate bone cement according to claim 1, characterized in that: The mass ratio of the tricalcium silicate powder to the copper selenide nanoparticles is 10000:1-40, preferably 10000:5-40, and more preferably 10000:10-20.

9. The copper selenide / tricalcium silicate bone cement according to claim 1, characterized in that: The liquid-to-solid ratio is 0.1-1 mL / g, preferably 0.5 mL / g.

10. Use of the copper selenide / tricalcium silicate bone cement according to any one of claims 1 to 9 in preparing a substitute material for treating bone tumors or postoperative bone transplantation.

Citation Information

Cited By

  • Multi-stage microporous titanium alloy loaded with nano copper selenide antibacterial peptide and preparation method of multi-stage microporous titanium alloy

    CN121265852A